Satirical News Reporting Strategies in the 2024 Indonesian General Election: A Case Study of Mojok.co’s “Terminal” and “Political Desk” Sections - Hanafi; Ervansyah, Fanzah Evan (Sinergi International Journal of Communication Sciences, 2025)
Mojok.co is one of Indonesia’s online media outlets that covered the 2024 General Election with a distinctive use of satire in its reporting. The application of satire as a linguistic and rhetorical strategy remains uncommon among Indonesian news organizations. This study explores how Mojok.co employs satire as a news reporting strategy, focusing on its implementation, challenges, and underlying rationale. Guided by Nunuk Parwati’s (2020) framework of news strategy. This research adopts a qualitative case study approach involving observation, in-depth interviews, and documentation of Mojok.co’s editorial practices. Three key informants and one supporting informant participated in the study. The analysis centers on three main dimensions: issue selection, news writing, and news presentation. The findings reveal that Mojok.co implements a threefold strategy: (1) selecting socially relevant and trending issues and framing them from distinctive perspectives; (2) employing a balanced, non-aggressive satirical tone in its writing and headlines; and (3) enhancing media branding through consistent satirical language and visually engaging presentation. To address ethical and editorial challenges, Mojok.co applies a strict article curation process, particularly in its Terminal and Political Desk sections. The study concludes that Mojok.co’s use of satire functions not only as a stylistic choice but also as a deliberate strategic communication tool that strengthens its brand identity and differentiates it from other Indonesian online media. This research contributes to the limited scholarship on satire in Indonesian journalism by situating it within the context of strategic news production and media branding.